Cholesterol remnants distribution in patients admitted for acute coronary syndrome. (3rd October 2022) - Cordero, A; Escribano, D; Alvarez-Alvarez, B; Martinon, J; Garcia-Rondeja, F; Rodriguez-Manero, M; Bertomeu-Gonzalez, V; Cazorla, D; Moreno-Arribas, J; Quintanilla, M A; Lopez Ayala, J M; Zuazola, P; et al.
Abstract: Background: Cholesterol remnants have been identified as one of leading lipid measurements associated with the incidence of coronary heart diseases. Nonetheless, there is scarce evidence on cholesterol remnants distribution in patients with acute coronary syndrome (ACS). Methods: We included all consecutive patients admitted for ACS in two different centers. Cholesterol remnants were calculated by the equation: total cholesterol minus low-density lipoprotein cholesterol (LDLc) minus high-density lipoprotein cholesterol (HDLc) and values ≥30 were considered high. Premature ACS was defined in patients presenting with age <55 for men or <65 for women. Correlation weres assessed by linear regression and predictive models were obtained after logistic binary regression. Results: We included 7, 479 patients, mean age 66.68 (13.02), 2, 062 (27.57%) women, mean body mass index (BMI) 28.60 (4.64) kg/m 2, 2088 (27, 92%) with diabetes and 2, 726 (36.45%) admitted for ST-elevation ACS. Median (interquartile range) remnants level was 28 mg/dl (21–39) and 3, 429 (45.85%) patients had levels ≥30 mg/dl. Significantly higher levels of remnants were observed in patients with diabetes, current smokers, BMI >30 kg/m 2, absence of previous cardiovascular disease or premature ACS. No gender differences were observed in remnants level. Age (r: −0.29) and BMI (r: 0.44) were the variables more strongly correlated. As shown in the figures, at any given age, the risk of having cholesterol remnants ≥30 increased with higher BMI. In-hospital mortality was 3.75% (280 patients). After adjustment by age, gender, previous cardiovascular disease and GRACE score, cholesterol remnants were not associated to higher mortality risk (OR: 0.89 95% CI 0.64–1.10; p=0.21) Conclusions: Elevated cholesterol remnants is highly prevalent in patients admitted for ACS and their levels inversely correlate with age and positively with body mass index. We propose a risk matrix for estimating the probability of having cholesterol remnants ≥30. Elevated cholesterol remnants were not associated to higher in-hospital mortality risk. Funding Acknowledgement: Type of funding sources: None.